Atmospheric circulation of brown dwarfs and directly imaged exoplanets driven by cloud radiative feedback: global and equatorial dynamics - Tan, X; Showman, AP (Oxford University Press, 2021)
Brown dwarfs, planetary-mass objects and directly imaged giant planets exhibit significant observational evidence for active atmospheric circulation, raising critical questions about mechanisms driving the circulation, its fundamental nature and time variability. Our previous work has demonstrated the crucial role of cloud radiative feedback on driving a vigorous atmospheric circulation using local models that assume a Cartesian geometry and constant Coriolis parameters. In this study, we extend the models to a global geometry and explore properties of the global dynamics. We show that, under relatively strong dissipation in the bottom layers of the model, horizontally isotropic vortices are prevalent at mid-to-high latitudes while large-scale zonally propagating waves are dominant at low latitudes near the observable layers. The equatorial waves have both eastward and westward phase speeds, and the eastward components with typical velocities of a few hundred  m s−1 usually dominate the equatorial time variability. Lightcurves of the global simulations show variability with amplitudes from 0.5 per cent to a few percent depending on the rotation period and viewing angle. The time evolution of simulated lightcurves is critically affected by the equatorial waves, showing wave beating effects and differences in the lightcurve periodicity to the intrinsic rotation period. The vertical extent of clouds is the largest at the equator and decreases poleward due to the increasing influence of rotation with increasing latitude. Under weaker dissipation in the bottom layers, strong and broad zonal jets develop and modify wave propagation and lightcurve variability. Our modelling results help to qualitatively explain several features of observations of brown dwarfs and directly imaged giant planets, including puzzling time evolution of lightcurves, a slightly shorter period of variability in IR than in radio wavelengths, and the viewing angle dependence of variability amplitude and IR colors.